2015
DOI: 10.1371/journal.pone.0129091
|View full text |Cite
|
Sign up to set email alerts
|

Lead Induces Apoptosis and Histone Hyperacetylation in Rat Cardiovascular Tissues

Abstract: Acute and chronic lead (Pb) exposure might cause hypertension and cardiovascular diseases. The purpose of this study was to evaluate the effects of early acute exposure to Pb on the cellular morphology, apoptosis, and proliferation in rats and to elucidate the early mechanisms involved in the development of Pb-induced hypertension. Very young Sprague-Dawley rats were allowed to drink 1% Pb acetate for 12 and 40 days. Western blot analysis indicated that the expression of proliferating cell nuclear antigen (PCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…Recent studies have provided adequate evidence regarding cardiovascular toxicity as a result of exposure to the single pollutants like SiNPs or Pb. 20,21 The complex mixtures could have interactive effect on the catalytic levels and transcriptional proteins. 22 Our previous studies have shown adverse toxicity after co-exposure, cardiovascular toxicity in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided adequate evidence regarding cardiovascular toxicity as a result of exposure to the single pollutants like SiNPs or Pb. 20,21 The complex mixtures could have interactive effect on the catalytic levels and transcriptional proteins. 22 Our previous studies have shown adverse toxicity after co-exposure, cardiovascular toxicity in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Although lead toxicity does not occur through a single unifying mechanism, its ability to substitute for Ca 2+ is a common factor in its toxicity [10]. Lead has been reported to induce activation of several cellular and molecular processes, such as apoptosis in cancer cell models and rats [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Different groups reported the assessment of cardiovascular damage induced by heavy metal exposure using H & E staining 35,36 . Cobbina and colleagues reported high toxicity as a result of co-exposure of metals in comparison with the individual metal exposure 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Pb and metal mixture treatment resulted in increased cardiac cell apoptosis. Previously, Xu and colleagues reported that Pb induces apoptosis in vascular and cardiac tissues 35 .…”
Section: Discussionmentioning
confidence: 99%